Modifikasi Sistem Cutting Body Ply pada Mesin Building Menggunakan PLC Allen-Bradley: [Modification of Bodyply Cutting System on Building Machines Using Allen-Bradley PLC] - Mario Gracio Anduinta Rhizma; Denson Siburian; Henri Uranus (FaST : Jurnal Sains dan Teknologi, 2025)
The process of body ply cutting system was previously performed manually, resulting in high cycle time and safety risks. The main issues include the lack of standardization in cutting pressure, cutting speed, and the risks associated with using a blade heated to 160-180°C. The proposed automated solution involves implementing proximity sensors, a Variable Frequency Drive (VFD), pneumatic solenoids, a three-phase motor, and a heating system with temperature control using a thermocouple. The system is controlled using an Allen-Bradley PLC and programmed with Studio 5000 Logix Designer. The results indicate that the modifications successfully reduce the cycle time per unit by 9.11% and increased production in the first shift by 7.6%. Bahasa Indonesia Abstract: Proses body ply cutting sebelumnya dilakukan secara manual, menyebabkan tingginya cycle time dan risiko keselamatan kerja. Beberapa masalah utama yang terjadi adalah tekanan pemotongan yang tidak standar, kecepatan pemotongan, dan risiko penggunaan pisau yang dipanaskan hingga 160-180°C. Solusi yang diusulkan adalah otomatisasi proses mencakup penerapan sensor proximity, Variable Frequency Drive (VFD), solenoid pneumatik, motor 3 fasa, serta pemanas dengan pengendalian suhu menggunakan termokopel. Sistem ini dikontrol menggunakan PLC Allen-Bradley dan diprogram melalui Studio 5000 Logix Designer. Hasil penelitian menunjukkan bahwa modifikasi ini berhasil mengurangi cycle time/unit sebesar  9,11%  dan  meningkatkan  produksi  pada  shift  1  sebesar  7,6%.